The bravest princess - Baker, E. D. (Baker,E. D. Wide-awake princess., 2015)
Sleeping Beauty's younger sister Annie must help her good friend, Snow White, as Snow White's father is trying to marry her off to any prince that comes to the kingdom. Annie will help Snow find the best prince for herself, but there could be an evil witch making trouble for them behind the scenes.